2020
DOI: 10.1186/s12967-020-02646-9
|View full text |Cite|
|
Sign up to set email alerts
|

The dysregulated innate immune response in severe COVID-19 pneumonia that could drive poorer outcome

Abstract: Background Although immune modulation is a promising therapeutic avenue in coronavirus disease 2019 (COVID-19), the most relevant targets remain to be found. COVID-19 has peculiar characteristics and outcomes, suggesting a unique immunopathogenesis. Methods Thirty-six immunocompetent non-COVID-19 and 27 COVID-19 patients with severe pneumonia were prospectively enrolled in a single center, most requiring intensive care. Clinical and biological characteristics (including T cell phenotype and function and plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 45 publications
(77 reference statements)
5
50
1
Order By: Relevance
“…al [ 9 ] CCL15 Lucas et. al [ 9 ] CCL10 Yao et al [ 54 ] CCL19 Balnis et al [ 60 ] CCL20 Chua et al ; Huang et al ; Gruber et al, Blot et al [ 7 , 21 , 50 , 65 ] CCL21 Lucas et. al [ 9 ] CCL22 Lucas et.…”
Section: Hints For Reading the Following Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…al [ 9 ] CCL15 Lucas et. al [ 9 ] CCL10 Yao et al [ 54 ] CCL19 Balnis et al [ 60 ] CCL20 Chua et al ; Huang et al ; Gruber et al, Blot et al [ 7 , 21 , 50 , 65 ] CCL21 Lucas et. al [ 9 ] CCL22 Lucas et.…”
Section: Hints For Reading the Following Sectionmentioning
confidence: 99%
“…The idea that CXCL10 and CCL2 should be regarded as “dominant” in the chemokine immune signature stems from the number of studies consistently reporting their crucial role in the onset of the cytokine storm of COVID-19 and from their relevance in determining specific features of this condition. Indeed, among the several chemokines which have been evaluated and found to be involved in COVID-19, CXCL10 and CCL2 were found to be the most up-regulated ones as compared to controls, showing different degrees of correlation with the viral load as well as with several peculiar symptoms (asthenia, dyspnea, anosmia) [ 5 , [7] , [8] , [9] , [10] , [11] , [21] , [22] , [23] , 29 , 36 , 37 , [44] , [45] , [46] , 49 , 54 , [65] , [66] , [67] ]. Most importantly, CXCL10 and CCL2 were identified to be rather good markers of disease severity since their circulating levels progressively increase in patients with moderate, mild and severe clinical manifestations.…”
Section: Chemokines Belonging To CC Familymentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author group. The investigators of the Lymphonie study group weren’t tagged as collaborators.…”
Section: Correction To: J Transl Medi (2020) 18:457 101186/s12967-02mentioning
confidence: 99%
“…The collaborators’ names are included in the ‘Acknowledgements’ section and listed below. The author group has been updated above and the original article [ 1 ] has been corrected.…”
Section: Correction To: J Transl Medi (2020) 18:457 101186/s12967-02mentioning
confidence: 99%
“…Early from the start of the pandemic caused by SARS-CoV-2, it was realized that patients with severe or critical illness present with profound immune dysregulation with the main features of lymphopenia, hyper-production of proinflammatory cytokines, hyper-ferritinemia and pro-inflammatory/anti-inflammatory imbalance (1)(2)(3)(4). An important question arising regarding the transition from severe COVID-19 pneumonia to critical illness and acute respiratory distress syndrome (ARDS) was whether this was identical in all patients, or whether different immune endotypes can be described in the severely ill patients (5).…”
Section: Introductionmentioning
confidence: 99%